Memperkenalkan Dunia Informatika dan Akuntansi Kepada Siswa-Siswi SMK Kesehatan Harapan Kita Sejahtera - April Tiodora Manik (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Kubu Raya Regency, especially the Sui Rengas area, is an area where the level of education is still very limited compared to other districts in West Kalimantan. Including the Kesehatan Harapan Kita Sejahtera Vocational School, where the number of students is still small. In addition to the number of students being still very small, the number of teaching staff is also small. It takes a lot of teaching staff to teach students at this vocational school. In terms of financing, Kesehatan Harapan Kita Sejahtera Vocational School is financed by School Operational Assistance funds. The purpose of this Community Service is to introduce the World of Informatics and Accounting to the students of Kesehatan Harapan Kita Sejahtera Vocational School.